Survivable virtual network mapping with differentiated services QoP - Guang-yuan LIU; Kai SHUANG; Sen SU (Tongxin xuebao)
The protection needs of virtual network are more and more diversified.So how to realize survival virtual net-work mapping of different needs is the important issue.The mathematical model of differentiated services QoP issue was formulated.Then a heuristic algorithm was proposed to solve it.The simulation results demonstrate the algorithm can sa-tisfy various virtual networks protection for users and decline the substrate network bandwidth cost compared with other algorithms.